Professional Learning Opportunities Regarding the Concept of Function in a Practice-based Teacher Education Program - Trevisan, André Luis (2020)
Teachers’ professional knowledge has been an active area in the field of mathematics education research in the last decades, but we still know very little regarding how teachers learn. This article aims to identify learning opportunities experienced by two teachers regarding mathematical and didactical knowledge for the teaching of function, in a context of practice-based learning. To this end, we analyze data from a practice-based teacher education program based on a cycle that incorporates three segments of teachers’ practice: planning, enacting and reflecting on a high school mathematics lesson, conducted from the perspective of inquiry-based teaching. We analyze two strands of the professional knowledge mobilized by the teachers, namely (i) the mathematics knowledge for teaching function, (ii) the knowledge for teaching practice, regarding function. The results indicate learning opportunities that emerged from the work done, regarding the use of the classroom as a teaching professional learning environment: the search for ways to encourage students to participate in the discussions; the recognition of the potential of the chosen lesson plan for the covariational approach , the importance of organizing mathematical discussion practices for students’ learning, organizing the time devoted to whole-class discussions and preparing for leading them and the potential of a class developed from the perspective of inquiry-based teaching.